Autopsy considerations from a science, technology and society perspectiva - Caridad Socorro Castro; Lian Roque Roque; Blanca Rosa Garcés Garcés; Magalys Oliver Cruz (Medisur)
Autopsy or necropsy is a method of anatomical-pathological study with a proven scientific and social value that arose in certain social conditions. Its development has been influenced by changing cultural, religious, ethical, political and economic values according to time and country, and as all technologies, is not exempt from social and environmental risks. In spite of this, in the reviewed literature, any work has been found in which a study is made on the subject of autopsy with a focus on science, technology and society. This is the purpose of the present work. For that, an updated review was carried out on the subject and it specifies the social conditions that made possible its emergence and development, the influence of culture and religion, its risks and, finally, some ethical considerations on its practice are made.